The Effect of Family Empowerment Model on Quality of Life in Children with Epilepsy in South of Iran, 2018: A Randomized Controlled Clinical Trial - Nemati, Hamid; Mahdavi Khanouki, Zahra; Ghasempour, Mohammad; Amirifar, Ahmad Ali; Alaei Karahroudi, Fatemeh; Gholami, Maryam (Iranian Journal of Child Neurology, 2021)
Abstract Objectives:Epilepsy is a chronic disease of the nervous system that significantly affects the performance and behavior of children. Epileptic children are at greater risk of cognitive and behavioral disorders than healthy children. Various factors associated with this disease affect the patients’ family. Materials & Methods:The present study is a randomized controlled clinical trial conducted to evaluate the effect of family empowerment on quality of life of epileptic children referred to the desired centers (Bessat Clinic affiliated to Kerman University of Medical Sciences and Imam Reza Clinic of Shiraz) in two experimental and control groups. 80 parents of these children were selected and studied, if they met the inclusion criteria of study. In this study, Quality of Life in Childhood Epilepsy Questionnaire (QOLCE) was used. It is completed by parents of these children. Results:The age of the studied children was 4 to 8 yrs. According to these results, there was a statistically significant difference between the two groups in the level of changes in all dimensions, so that the mean score of quality of life in different factors increased in the experimental group compared to the control group (P <0.05 in all dimensions). Conclusion:Implementing the family-centered care plan by care providers, based on patient-family support relationships, identifying their strengths and weaknesses, prioritizing the services provided, and an effective interaction with the health team increase the family and staff satisfaction, reduce the costs, and improve the outcome of the disease.